Corporate sustainability and value creation: The case of the “Dow jones sustainability index” - Zago, Ana Paula Pinheiro; Jabbour, Charbell José Chiappetta [UNESP]; Bruhn, Nádia Campos Pereira (FapUNIFESP (SciELO), 2018)
Choosing an enterprise that will be part of Dow Jones Sustainability Index (DJSI) raises some expectations concerning this conquest benefits. We hope that the investment on sustainable development and the inclusion of the company in this select group bring economic and strategic benefits that can reflect in the company market valorization. However, the correlation between social, environmental and financial development is quite complex. In this context, this paper aims to verify whether the inclusion of an enterprise in DSJI list, which presupposes a high social and environmental performance, provides it with greater financial return. We use the case study method in order to investigate the existence of abnormal returns when disclosing the information of the company inclusion in the list, as well to analyze the hypothesis that market has positive expectations concerning to DSJI participation. This study included one hundred and fifty-four companies listed in DSJI that trade their shares on the New York Stock. The results show no effect and do not confirm the greater return hypothesis, but neither do they indicate a reduction in financial performance associated do this fact.
Keywords: Corporate sustainability; Dow jones sustainability index; Financial performance